2014
DOI: 10.1007/s10461-014-0939-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors Enhancing Utilization of and Adherence to Prevention of Mother-to-Child Transmission (PMTCT) Service in an Urban Setting in Kenya

Abstract: Despite expansive scale-up of prevention of mother-to-child transmission (PMTCT) of HIV services in Kenya over the last decade, Kenya remains one of the countries contributing to high numbers of children living with HIV globally and is among the 22 PMTCT global plan priority countries. Using structured and in-depth interviews this study examined enabling factors that enhance utilization of and adherence to PMTCT services in an urban setting in Kenya. HIV-positive birthmothers (N = 55) whose infants were HIV-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…Many distinct factors contributed to how a woman assessed her individual circumstances and overcame barriers to engage in care and follow PMTCT guidelines. Consistent with previous studies, our findings suggest that uptake of PMTCT services can be facilitated by accurate knowledge and understanding of HIV and PMTCT [ 8 10 ], positive disclosure experiences, especially with a male partner who knows his own status, and active support from both the community and male partners [ 24 ]. Our study also found that male partners had a significant influence on women’s participation in PMTCT [ 6 , 7 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many distinct factors contributed to how a woman assessed her individual circumstances and overcame barriers to engage in care and follow PMTCT guidelines. Consistent with previous studies, our findings suggest that uptake of PMTCT services can be facilitated by accurate knowledge and understanding of HIV and PMTCT [ 8 10 ], positive disclosure experiences, especially with a male partner who knows his own status, and active support from both the community and male partners [ 24 ]. Our study also found that male partners had a significant influence on women’s participation in PMTCT [ 6 , 7 , 9 , 10 ].…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies on attrition from PMTCT programs in African settings have primarily gathered data from HIV-positive women only, and identified discrete factors that influence their participation in PMTCT services. Commonly cited barriers include stigma associated with HIV [ 6 9 ], limited understanding of PMTCT [ 8 10 ], fear of disclosure and lack of support from male partners [ 6 , 7 , 9 , 10 ], and dissatisfaction with clinic programs, staff, and confidentiality [ 6 , 8 , 10 ]. There has been less in-depth analysis on the complex relationships between these barriers, and how external influences, including the community, male partners, and healthcare workers, contribute toward a woman’s decisions regarding enrollment and participation in PMTCT services.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to what has been documented in a previous study that knowing someone who is living with HIV enables those infected to accept their HIV status because of the inner comfort they feel knowing that someone shares their experience [25, 68]. This finding echoes earlier work showing that peer support groups play an important role in helping women living with HIV to understand HIV and PMTCT programs leading to retention in care and adherence to ART [6972]. On the other hand participants in our study did not feel comfortable disclosing their status to community members for fear of stigma and ridicule contrary to what has been reported in a previous study that community members play a role in helping WLWH adhere to their medication and cope with the illness [70].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings therefore highlight the need for health care workers to utilize a more empathic approach to the issue of non-adherence in their prevention of vertical transmission counseling sessions, recognising the positive intentions and psychological stress that HIV infected mothers undergo in making infant feeding choices. Ultimately this approach may also help to promote adherence to recommended practices [62]. …”
Section: Discussionmentioning
confidence: 99%